EFEKTIVITAS PENGGUNAAN KULIT JERUK PURUT SEBAGAI PENGAWET ALAMI IKAN - Darwanto, Agus; Devi Nur Fadilah; Nur Fadil 'Ulum (Jurnal Inovasi Daerah, 2024)
Kaffir lime peel (Citrus hystrix) is often discarded after extracting its juice, turning it into waste that is not utilized. In fact, the antibacterial properties in kaffir lime peel are quite good. The purpose of this research is to determine the effectiveness of using kaffir lime peel as a natural preservative for fish compared to ice, betel leaves, kaffir lime leaves, lime leaves, sweet orange leaves, lime peel, and sweet orange peel. Data collection was done using sensory tests, TVB-N tests, and Aerobic ALT tests. Data analysis was carried out using comparative descriptive analysis, ANOVA tests, and BNT/LSD tests. The use of kaffir lime peel as a fish preservative involved cutting the lime peel into small pieces, drying, and grinding it into powder. The effectiveness of kaffir lime peel in preserving fish was significantly better than ice or other natural materials such as betel leaves, kaffir lime leaves, lime leaves, sweet orange leaves, lime peel, and sweet orange peel. ANOVA test analysis showed a p-value is less than 0.05, concluding that there is a significant effect of using kaffir lime peel as a fish preservative. Based on the BNT test analysis, there is a significant difference between the use of kaffir lime peel compared to ice and other natural preservatives. The effect of kaffir lime peel on maintaining fish texture was 41.12%, eye clarity was 72.79%, gill color was 13.83%, fish scale color was 66.76%, and odor (aroma) was 66.73%. The results of the TVB-N test showed a value of 232.58 mg per 100 grams, which was better than ice with a TVB-N value of 262 mg per 100 grams. Meanwhile, the microbiological results using the Aerobic ALT test showed a value of 4.021 log cfu per gram, much better than ice, which had an Aerobic ALT value of 4.146 log cfu per gram. Thus, the use of kaffir lime peel is the most effective in preserving fish compared to ice and other natural materials.